High-output-impedance current-mode electronically tunable universal filter using single CFTA - Sirirat, Jamaree; Prasertsom, Danucha; Tangsrirat, Worapong (My University, 2010)
This paper presents a canonical current-mode biquad filter with three inputs and one output. The presented filter employs a single current follower transconductance amplifier (CFTA) and a minimum of passive components, i.e., one resistor and two grounded capacitors. It is capable of generating all the five standard biquadratic filtering functions and suitable for current-mode cascading by possessing high-output impedance. Also, the proposed filter can be tuned electronically by an external bias current of the CFTA. The circuit is analyzed for the non-idealities of the used CFTA and possesses attractive low sensitivity performance. PSPICE simulation results are found to be in good agreement with the presented theory. ©2010 IEEE.